أحمد بن بلة و الفكر القومي الناصري و ملامح تجسيده في قيادة الدولة الجزائرية - لوصيف, سفيان (جامعة الوادي - University of Eloued, 2018)
Summary: The article deals with the study and personalization of Ahmed Ben Bella, the first president of independent Algeria, which was greatly influenced by the thought of Egyptian President Gamal Abdel Nasser. Since the beginning of the Algerian revolution, Ben Bella has considered him the leader of the Arab unity project. The Algerian independent state, especially the issue of dispossession of the French colonial heritage based on the French project, and worked to restore the characteristics of Algerian personality, especially the issue of Arabization, the latter will know the difference between different political and cultural elites.
مقال
Keywords: أحمد بن بلة، جمال عبد الناصر، الفكر القومي